Timaeus' Explanation of Sense-Perceptual Pleasure. (9th December 2014) - Wolfsdorf, David
Abstract: Much has been written about Plato's accounts of pleasure in Republic 9 and Philebus, almost nothing about his account in Timaeus . But with respect to sense-perceptual pleasure specifically, the account in Timaeus is unique and extremely informative. This paper examines, in turn, the physiology and the psychology of sense-perceptual pleasure, focusing on the text at 64a2–65b3, but drawing on a wide range of passages from elsewhere in the dialogue. The paper concludes with a further suggestion: that Timaeus is implicitly committed to a distinction between two kinds of perceptual pleasure, sense-perceptual pleasure and 'brute' pleasure.